Understanding Greed in Literature: A Dialogue of Textual and Social Interpretations of Money - Saifur Rohman (Aksara, 2025)
This paper focuses on the ethical issues facing Indonesian people in literature and reality. The material object is novel 86 ("eight six") by Okky Madasari and interpretation of money in Indonesian government. The hypothesis that the money becomes the driving force of a corrupt and deceitful figure. If this imagination is reflected in past authors, money as a plot mover was once written by Pramoedya Ananta Toer in the novel Corruption (first published in 1954). The impoverished Bakir had worked as a lowly employee for many years until his fortunes changed after selling office equipment to enrich himself. On the other hand, in colonial times, money moved the flow towards a disciplined and good  figure. F Wigger in Lelakon Raden Beij Soerio Retno (1901) has described a good figure of the establishment class not to use money of. the country. Similarly, Toto Sudarto Bachtiar who wrote a poem entitled "Notes for the Old Days" (1958) treats money as a provision of life and doing good. In conclusion, Indonesia people are still tempted with money so ethically become part of hedonism human being.  In reality, Indonesia ranks top when talking about bad and gets the bottom rank when talking about good. Reading novel 86 (Eight Six) is to read a context that refers to the problem of civil administration.  Based on an analysis of texts, new reality of the national spirit should have to build a new spirit that is replaced greedy to be honor and shame. AbstrakMakalah ini berfokus pada isu-isu etika yang dihadapi masyarakat Indonesia dalam karya sastra dan kenyataan. Objek materialnya adalah novel 86 ("Delapan Enam") karya Okky Madasari dan interpretasi tentang uang dalam pemerintahan Indonesia. Hipotesisnya adalah uang menjadi motor penggerak tokoh yang korup dan suka menipu. Jika imajinasi ini tecermin pada pengarang-pengarang terdahulu, uang sebagai penggerak alur pernah ditulis oleh Pramoedya Ananta Toer dalam novel Korupsi (terbit pertama kali tahun 1954). Tokoh Bakir yang miskin sempat bekerja sebagai pegawai rendahan selama bertahun-tahun hingga peruntungannya berubah setelah menjual peralatan kantor untuk memperkaya diri. Di sisi lain, pada masa kolonial, uang menggerakkan alur menuju sosok yang disiplin dan tegas. F Wigger dalam Lelakon Raden Beij Soerio Retno (1901) menggambarkan sosok yang tegas dari kalangan penguasa agar tidak menggunakan uang negara. Begitu pula Toto Sudarto Bachtiar yang menulis puisi berjudul "Catatan untuk Masa Lalu" (1958) memperlakukan uang sebagai bekal hidup dan berbuat baik. Kesimpulannya, masyarakat Indonesia masih tergoda dengan uang sehingga secara etika menjadi bagian dari manusia hedonisme. Kenyataannya, Indonesia menduduki peringkat teratas ketika berbicara tentang keburukan dan mendapat peringkat terbawah ketika berbicara tentang kebaikan. Membaca novel 86 adalah membaca konteks yang mengacu pada masalah administrasi masyarakat. Berdasarkan analisis teks, kenyataan baru tentang semangat kebangsaan seharusnya membangun semangat baru yang menggantikan keserakahan menjadi bentuk kehormatan dan rasa malu.